Cybersecurity : a Comprehensive Guide to Getting Started in Cybersecurity. - Ozkaya, Erdal (Packt Publishing, Limited, 2019)
Cybersecurity jobs confines from basic configuration to advanced systems analysis and defense assessment. Cybersecurity: The Beginner's Guide provides thefundamental information you need to understand the basics of the field, identify your place within it, and start your Cybersecurity career.